2021
DOI: 10.1001/jamanetworkopen.2021.27172
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Ferritin Levels and Methylprednisolone Treatment With Outcomes in Nonintubated Patients With Severe COVID-19 Pneumonia

Abstract: IMPORTANCE Serum ferritin, an acute phase marker of inflammation, has several physiologic functions, including limiting intracellular oxidative stress. Whether the effectiveness of corticosteroids differs according to serum ferritin level in COVID-19 has not been reported. OBJECTIVE To examine the association between admission serum ferritin level and methylprednisolone treatment outcomes in nonintubated patients with severe COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Furthermore, women had a positive trend between serum ferritin and the number of adverse body compositions, which was not seen in men. Similar to our study, a few studies on the association between serum ferritin and metabolic disorders, including obesity, sarcopenia, and osteopenia, have shown a significant association in women [ 21 , 29 , 47 ]. There are some possible explanations for gender-specific differences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, women had a positive trend between serum ferritin and the number of adverse body compositions, which was not seen in men. Similar to our study, a few studies on the association between serum ferritin and metabolic disorders, including obesity, sarcopenia, and osteopenia, have shown a significant association in women [ 21 , 29 , 47 ]. There are some possible explanations for gender-specific differences.…”
Section: Discussionsupporting
confidence: 91%
“…[ 40 ]. This oxidative stress may increase susceptibility to apoptosis during the development of sarcopenia [ 18 , 29 ] and lead to inflamed adipose tissue during the aggravation of obesity [ 41 ]. The mechanism of OSO is thought to begin with mesenchymal stem cell lineage deregulation [ 1 ], and a recent study reported that the osteogenic commitment and differentiation of mesenchymal stem cells is hindered through the induction of ferritin by excess iron.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We here sought to assess the incidence of hyperferritinemia in patients with CAP hospitalized in a general ward and to determine its association with disturbances in key host response pathways implicated in the immunopathology of pneumonia and sepsis. We considered this of interest, as circulating ferritin levels have been and are used as inclusion criteria in trials evaluating immunomodulatory therapies in acute infections and may assist in identifying patients who might benefit from such therapies [ 13 , 23 ] (clinicaltrials.gov identifiers NCT04530578, NCT04341675, NCT04443881, and NCT04990232). We performed 2 analyses, stratifying patients according to cutoff ferritin levels of ≥500 ng/mL (used in studies in patients with CAP caused by SARS-CoV2: NCT04530578, NCT04341675, and NCT04443881) or ≥250 ng/mL (around the normal reference value in most laboratories).…”
Section: Discussionmentioning
confidence: 99%